The Changing Demographic Environment and Its Relevance for International Financial Services Providers - Michaela Rudolf; Johannes Störmer; Sophia Wahl; Sebastian Zwiesler; Klaus Mühlbäck (ISM Research Journal, 2018)
Demography in Germany is changing and companies have to adapt their marketing communication accordingly. Understanding the changing environment and especially its customers is becoming a main concern for firms. This market research study had two objectives. The first objective was to gain a thorough understanding about the financial service customers in the German market. Especially in terms of consumers' needs, information behaviour and motivation to invest, mapped on the triangle of investment. The second objective was to evaluate a life phase model, which was created to segment the German market. Two empirical researches were conducted to cover the objectives. A qualitative study with focus groups, to gain information about consumer needs and their underlying motivation. Second, a quantitative approach, to gain insights on information behaviour and motives as well as the differences throughout the life span of customers. An online survey questioning 527 individuals was developed to receive a valid set of data. The overall findings are consistent with prior literature, as there were no solid indications of differences found between the distinctive age groups, in terms of motivation and information behaviour. Further, there was no evidence for the validity of the life phase model. That is why a new segmentation, based on a cluster analysis over a broad variety of suitable variables, had been conducted. As a result, four independent customer segments were generated to create an advanced description for each segment.
Keywords: 650